Bibliometric Analysis of Micro-teaching Model Research Trends in 2013-2023 - Jusuf Blegur; Amung Ma'mun; Agus Mahendra; I Made Sriundy Mahardika; Zuvyati Aryani Tlonaen (Journal of Innovation in Educational and Cultural Research, 2023)
A comprehensive literature meta-study determines the accuracy of diagnosing past studies. It will influence plans to develop more meaningful and impactful future studies. The research aims to inspect the development of the publication of research articles on the micro-teaching model. Article data was collected using the Publish or Perish application, with the title words "Microteaching model" and "Micro-teaching model" from a search to inspect Google scholars within the last ten years, then verified using the Mendeley Reference Manager and analyzed with the VOSviewer tool. The inspection results find that the micro-teaching model research has not experienced significant development. The rationale is that of the 62 papers analyzed, on average, they are still developing and discussing sectoral micro-teaching models for mastering and improving teaching skills. Future research is needed to develop a micro-teaching model that supplements other skills (including analytical thinking, transformational leadership, and others). This research contributes as an evaluation of the publication database of articles on the micro-teaching model that advanced researchers can use to create more significant future research on classroom learning organizations that are more impactful, meaningful, and futuristic in preparing the competence of prospective teachers.